2011
DOI: 10.1586/erm.10.107
|View full text |Cite
|
Sign up to set email alerts
|

RT-PCR/electrospray ionization mass spectrometry approach in detection and characterization of influenza viruses

Abstract: Reverse-transcription PCR (RT-PCR) coupled with electrospray ionization mass spectrometry (ESI-MS) is a high-throughput nucleic acid-based technology that relies on the accurate measurement of the molecular weight of PCR amplicons that can be used to deduce the base counts (number of As, Gs, Cs and Ts) of DNA. These amplicons represent highly variable regions with information-rich sequences, which are flanked by broad-range primers designed based on highly conserved loci. This technology was first introduced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 47 publications
0
34
0
Order By: Relevance
“…For example, clade distribution of A(H3N2) viruses circulating between 1997 and 2006 was studied using the RT-PCR/electrospray ionization mass spectrometry (ESI MS), an approach based on the identification of unique nucleotide compositions of less variable internal genes (25). Although powerful, this approach is limited by access to costly equipment and requires an external database (Abbott Molecular, Carlsbad, CA) for data analysis and interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, clade distribution of A(H3N2) viruses circulating between 1997 and 2006 was studied using the RT-PCR/electrospray ionization mass spectrometry (ESI MS), an approach based on the identification of unique nucleotide compositions of less variable internal genes (25). Although powerful, this approach is limited by access to costly equipment and requires an external database (Abbott Molecular, Carlsbad, CA) for data analysis and interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…The PCR/ESI-MS method has been used to simultaneously identify and type multiple clinically relevant pathogens including viruses, bacteria, and fungi from clinical and environmental samples. [19][20][21]29,30 Molecular methods are very sensitive, and we avoided false positives by using a calibration standard of 500 copies for each primer pair targeted to ribosomal DNA and 100 genome copies for each primer pair targeted to genes encoding housekeeping proteins, which roughly matched the relative abundance of ribosomal operons to housekeeping genes. Because the calibration standard competes with the target organism DNA for amplification, this effectively established a threshold for detection, whereby low levels of endogenous DNA were not detected as a false positive.…”
Section: Discussionmentioning
confidence: 99%
“…Among adult patients with ARI in one study using this type of testing in the United States in 2012-2013, 5% to 8% were found to sustain viral coinfections, to include influenza, HCoVs, RSV and HRV [35]. One influenza typing kit based on the RT-PCR electrospray ionization mass spectrometry (PCR-ESI-MS) platforms allows detection of all 16 hemagglutinin and 9 neuraminidase subtypes, [36] as well as detection of drift of specific genes over time [36][37][38][39]. Because of its ability to detect newly emerging recombinant, drifted, or shifted influenza viruses, the PCR-ESI-MS typing analysis can be useful in detecting newly emerging influenza strains [40].…”
Section: Diagnosismentioning
confidence: 99%